2009
DOI: 10.1128/jb.00888-09
|View full text |Cite
|
Sign up to set email alerts
|

The Multifaceted Proteins MvaT and MvaU, Members of the H-NS Family, Control Arginine Metabolism, Pyocyanin Synthesis, and Prophage Activation in Pseudomonas aeruginosa PAO1

Abstract: The MvaT and MvaU proteins belonging to the H-NS family were identified as DNA-binding proteins that interact with the regulatory region of the aotJQMOP-argR operon for arginine uptake and regulation. Recombinant MvaT and MvaU proteins were purified, and binding of these purified proteins to the aotJ regulatory region was demonstrated using electromobility shift assays. Polyclonal antibodies against purified MvaT and MvaU were prepared and employed in supershift assays to support these observations. Knockout m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 35 publications
(37 reference statements)
5
44
1
1
Order By: Relevance
“…A previous report demonstrated that cells of P. aeruginosa strain PAO1 that contain deletions of both the mvaT and mvaU genes are viable (31). This finding appears to contradict our findings that MvaT and MvaU are essential in the absence of the partner regulator (9) (Fig.…”
Section: Identification Of Transposon Insertion Mutants That Toleratecontrasting
confidence: 99%
See 1 more Smart Citation
“…A previous report demonstrated that cells of P. aeruginosa strain PAO1 that contain deletions of both the mvaT and mvaU genes are viable (31). This finding appears to contradict our findings that MvaT and MvaU are essential in the absence of the partner regulator (9) (Fig.…”
Section: Identification Of Transposon Insertion Mutants That Toleratecontrasting
confidence: 99%
“…These findings resolve the apparent discrepancy between our earlier findings obtained through protein depletion, that the loss of both MvaT and MvaU cannot be tolerated (9), and the previous demonstration that cells containing deletions of both mvaT and mvaU are viable (31). We note that, consistent with the findings reported here, activation of Pf4 prophage was observed previously in cells containing deletions of both mvaT and mvaU (31).…”
Section: Discussionsupporting
confidence: 88%
“…An mvaT mutant exhibits more production of PA-IL lectin and pyocyanin, reduced biofilm formation and swarming motility, and increased drug resistance (53,204). The observation that mvaT and mvaU single mutants increase pyocyanin synthesis while an mvaT mvaU double mutant abolishes pyocyanin and PQS production suggests that these regulators work in different ways to control pyocyanin production, with one involving PQS production and the other directly controlling pyocyanin synthesis (117). In addition to the four genes involved in PQS biosynthesis, the pqsABCDE operon contains a fifth, pqsE (PA1000), encoding a protein with a metallo-␤-lactamase fold (62) that is not required for PQS synthesis (71).…”
Section: Pqsmentioning
confidence: 99%
“…Two H-NS family proteins that have been studied in P. aeruginosa are MvaT and MvaU, which act coordinately and preferentially bind regions of the P. aeruginosa chromosome corresponding to accessory genetic elements (37). Not surprisingly, then, double mutation of mvaT and mvaU results in activation of chromosomally integrated filamentous Pf4 prophage (126). The extent of H-NS-mediated repression of horizontally transferred genes has yet to be determined.…”
Section: Hgt and Evolution Of The Accessory Genomementioning
confidence: 99%